Влияние функции питания на формирование головной кишки позвоночных. I. Первичноводные позвоночные - Гиммельрейх, Г.А. (Вестник зоологии, 1968)
In phylogenesis of the cephalic intestine in primary water vertebrates some turn-ing points took place which can be characterized as aromorphoses: a) obtaining active compression as a result of the development of visceral musculature; b) obtaining active extension owing to the contact of somatic muscles with visceral arches; c) transforma-tion of the third visceral arch into the mandibles; d) transformation of the forth visceral arch into the hyoid one; e) transformation of the dorsal constrictor of the mandibular arch into a dilator of visceral apparatus and connected with this the presence of secondary four joints of the hyoid arch; f) the development of snapping mandibles on the basis of a specialized sticking visceral apparatus. An evolution of the cephalic intestine is determined by intensification of its both main functions: nutrition and respiration, but the activization of nutrition which appears as a result of adaptability to the varying environmental conditions is of main impor-tance in the progressive morphofunctional transformations of the cephalic intestine.